Comics Media (Mathematics Mission Box) to Improve Understanding of the Concepts OF LCM and GCF in Elementary Schools - Tramelia Salsabela; Wulan Sutriyani; Abdullah Efendi (LPPM Undiksha, 2025)
Mathematics is considered a difficult subject, leading to boredom and a low understanding of basic mathematical concepts. Difficulty understanding the concepts of LCM and GCF, particularly when working on story problems, is a major obstacle experienced by students. This study aims to identify the development, effectiveness, and practicality of the KOMIKA (Mathematics Mission Box) media in improving understanding of the concepts of LCM and GCF in elementary schools. This study uses the method Research and Development (RnD) by adopting the ADDIE development model. The expert trial involved two parties: two material experts and two media experts. Meanwhile, the product trial involved 31 fifth-grade elementary school students as the main subjects. Data analysis techniques used qualitative and quantitative analysis. The results of the study showed indication that KOMIKA media has proven successful in strengthening conceptual understanding of KPK and FPB at elementary school level. Therefore, it is concluded that the KOMIKA (Mathematics Mission Box) media is valid, effective, and practical to use. The implication of this research is that the development of KOMIKA media as an innovation in learning activities will facilitate students in building and improving their conceptual understanding.